2016
DOI: 10.1080/13803395.2016.1168780
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus antibody titers associated with cognitive dysfunction in an asymptomatic community-based sample

Abstract: Background Hepatitis C virus (HCV) infection is associated with cognitive dysfunction in clinic-based studies. The risk could be attributed to factors such as antiviral medications, substance abuse or coincidental infection. Aim To evaluate cognitive function in relation to HCV antibody titers in a community-based sample of asymptomatic individuals at low risk for substance abuse. Methods Adults were ascertained from a community in Mansoura, Egypt, where HCV is endemic (n=258). Cognitive performance was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…The additive effects of HIV and chronic smoking led to the poorest cognitive performance in our HIV+Smoker group, across the four groups, which is also consistent with an earlier study that found worse memory and global functioning scores in HIV+Smokers compared to HIV+ non-Smokers (Bryant et al, 2013). However, the HIV+Smokers in this earlier study also had a higher prevalence of hepatitis C virus co-infection, which might have contributed to the poorer cognitive performance (Fialho et al, 2016; Ibrahim et al, 2016), but we excluded such participants in the current study. Since nicotine is neuroprotective (Vieira-Brock et al, 2015), the additive adverse effects of tobacco smoking on cognitive performance in HIV+ participants may be due to chronic tobacco use’s negative influence on cardiovascular risk factors, which in turn may contribute to poorer cognition in HIV+ patients (Becker et al, 2009; Fabbiani et al, 2013), Since smoking cessation may decrease the cardiovascular risks in HIV+ patients (Petoumenos et al, 2011), future studies should evaluate whether smoking cessation may also lead to improved cognition in HIV+Smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The additive effects of HIV and chronic smoking led to the poorest cognitive performance in our HIV+Smoker group, across the four groups, which is also consistent with an earlier study that found worse memory and global functioning scores in HIV+Smokers compared to HIV+ non-Smokers (Bryant et al, 2013). However, the HIV+Smokers in this earlier study also had a higher prevalence of hepatitis C virus co-infection, which might have contributed to the poorer cognitive performance (Fialho et al, 2016; Ibrahim et al, 2016), but we excluded such participants in the current study. Since nicotine is neuroprotective (Vieira-Brock et al, 2015), the additive adverse effects of tobacco smoking on cognitive performance in HIV+ participants may be due to chronic tobacco use’s negative influence on cardiovascular risk factors, which in turn may contribute to poorer cognition in HIV+ patients (Becker et al, 2009; Fabbiani et al, 2013), Since smoking cessation may decrease the cardiovascular risks in HIV+ patients (Petoumenos et al, 2011), future studies should evaluate whether smoking cessation may also lead to improved cognition in HIV+Smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are limited data on the prevalence of T. gondii and associated risk factors in women during pregnancy. In different Egyptian localities, between 1993 and 2016, the prevalence of toxoplasma antibodies were ranged between 27% and 68% in pregnant women [ 236 , 239 , 245 , 247 , 248 , 249 , 250 , 251 , 252 , 253 ], 26% in cerebrospinal fluid of meningoencephalitis patients [ 254 ], 59.6% in asymptomatic blood donors [ 255 ].…”
Section: Parasitic Zoonosismentioning
confidence: 99%
“…The results of Giemsa-stained smears revealed the presence of Toxoplasma's tachyzoites in 7% of the examined samples. Hassan et al (2020) The seroprevalences of Toxoplasma infections in humans varied from 27 % to 68% in asymptomatic pregnant women (Ghoneim et al, 2010;El Deeb et al, 2012;Ibrahim et al, 2016b), 26% in cerebrospinal fluid of patients with meningoencephalitis (Mabrouk and Dahawi, 1991), and 59.6% in blood donors without signs (Elsheikha et al, 2009). It has been reported a higher percentage of toxoplasmosis among Egyptians with liver cirrhosis (El-Henawy et al, 2015;El-Sayed et al, 2016).…”
Section: Quailsmentioning
confidence: 99%